A study of students' interests in reading in a second language / Zurina Khairuddin - Khairuddin, Zurina (2012)
Reading interests is important in enhancing students' success in school and out of it. Hence, students need to have high reading interests. The purposes of this study were to identify students' reading interests in reading second language materials, to examine the differences in students' reading interests based on genders, academic streams and household monthly income as well as to investigate the relationship between parents' involvement in reading with students' reading interest. This study was carried out among 86 Form Four students in Kuala Terengganu with simple random sampling using a 29-item questionnaire adapted and adopted from Marrero (2009). Data were analysed as well as presented in the form of frequency, means, standard deviation, independent t - test, ANOVA, Post Hoc Tests and correlations. From this study, it is found that students have relatively low interests in reading English materials. Furthermore, there is significant difference between male and female students and meanwhile there is no significant difference between pure science and arts students as well as among the household monthly income groups with regards to their reading interests. Finally, this study revealed that there is moderate relationship between parents' involvement in reading and students' reading interests in reading second language materials. From these findings, it can be suggested that stakeholders should take action with regards to developing and enhancing male students' reading interests. Furthermore, although parents' involvement in reading moderately influences students' reading interests, it still affects students' interests. Hence, parents should get involved with students' reading. It is hoped that the finding of this study would enlighten the relevant literature of the area.